2021
DOI: 10.1186/s12966-020-01066-8
|View full text |Cite
|
Sign up to set email alerts
|

Networks of stress, affect and eating behaviour: anticipated stress coping predicts goal-congruent eating in young adults

Abstract: Background Many people aim to eat healthily. Yet, affluent food environments encourage consumption of energy dense and nutrient-poor foods, making it difficult to accomplish individual goals such as maintaining a healthy diet and weight. Moreover, goal-congruent eating might be influenced by affects, stress and intense food cravings and might also impinge on these in turn. Directionality and interrelations of these variables are currently unclear, which impedes targeted intervention. Psychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 96 publications
1
43
0
3
Order By: Relevance
“…Individuals were recruited for the RCT through study announcements via e-mail at several universities in Austria and Germany, Facebook groups, Twitter, and by word of mouth. Similar to previous study inclusion criteria (13), agreeing to one of the following two questions enabled individuals to take part in the study: 1) 'Do you currently pay attention to your nutrition to maintain or reduce your body weight'? and 2) 'Do you currently cut down on your food intake to maintain or reduce your body weight'?…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Individuals were recruited for the RCT through study announcements via e-mail at several universities in Austria and Germany, Facebook groups, Twitter, and by word of mouth. Similar to previous study inclusion criteria (13), agreeing to one of the following two questions enabled individuals to take part in the study: 1) 'Do you currently pay attention to your nutrition to maintain or reduce your body weight'? and 2) 'Do you currently cut down on your food intake to maintain or reduce your body weight'?…”
Section: Methodsmentioning
confidence: 99%
“…The temporal network structure is estimated by considering all variables of interest and their unique lagged associations among each other (26). A network analysis study by our group found that higher anticipated stress coping preceded higher goal-congruent eating (13).…”
Section: Accounting For Variability Within and Between Individuals In Ema Data: Multilevel Models And Network Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several previous studies on eating behaviour (Kolanowski & Trafialek, 2021;Korinth, Schiess & Westenhoefer, 2010;Pannicke, Kaiser, Reichenberger & Blechert, 2021;Scaglioni, Salvioni & Galimberti, 2008;Wardle, Marsland, Sheikh, Quinn, Fedoroff & Ogden, 1992;Webber, Hill, Saxton, Van Jaarsveld & Wardle, 2009). However, there are limited studies on the intention to practice healthy eating behaviour (e.g.…”
Section: Intention To Practise Healthy Eating Behaviourmentioning
confidence: 99%